The ARCANE project: How an ecological dynamics framework can enhance performance assessment and prediction in football - Couceiro, M. S.; Dias, G.; Araújo, D.; Davids, K. (Sports Medicine, 2016)
This paper discusses how an ecological dynamics framework can be implemented to interpret data, design practice tasks and interpret athletic performance in collective sports, exemplified here by research ideas within the Augmented peRCeption ANalysis framEwork for Football (ARCANE) project promoting an augmented perception of football teams for scientists and practitioners. An ecological dynamics rationale can provide an interpretation of athletes` positional and physiological data during performance, using new methods to assess athletes` behaviours in real-time and, to some extent, predict health and performance outcomes. The proposed approach signals practical applications for coaches, sports analysts, exercise physiologists and practitioners through merging a large volume of data into a smaller set of variables, resulting in a deeper analysis than typical measures of performance outcomes of competitive games.